2012
DOI: 10.1002/hep.24816
|View full text |Cite
|
Sign up to set email alerts
|

Connecting liver and gut: Murine liver sinusoidal endothelium induces gut tropism of CD4+ T cells via retinoic acid

Abstract: Gut-activated T cells migrating into the liver can cause extraintestinal manifestations of inflammatory bowel disease. T cells acquire a gut-homing phenotype dependent on retinoic acid (RA) provided by intestinal dendritic cells (DC). We investigated whether liver antigen-presenting cells can induce gut tropism supporting an enterohepatic lymphocyte circulation. Priming of CD4+ T cells by liver sinusoidal endothelial cells (LSEC) supported migration into gut and gut-associated lymphoid tissue. As observed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Hepatic and ileal mRNA levels were normalized to the mRNA level of glyceraldehyde-3-phosphate dehydrogenase ( Gapdh ). Gapdh is considered a house keeping gene and frequently used as a reference gene [32, 33]. In addition, it has been shown that Gapdh is one of the most stable reference genes [34].…”
Section: Methodsmentioning
confidence: 99%
“…Hepatic and ileal mRNA levels were normalized to the mRNA level of glyceraldehyde-3-phosphate dehydrogenase ( Gapdh ). Gapdh is considered a house keeping gene and frequently used as a reference gene [32, 33]. In addition, it has been shown that Gapdh is one of the most stable reference genes [34].…”
Section: Methodsmentioning
confidence: 99%
“…17 In our previous study, we proved that immune cells including T and B lymphocytes could shuttle from mesenteric lymph nodes to the liver and promote NAFLD. Studies have shown the existence of enterohepatic lymphocyte circulation.…”
Section: Introductionmentioning
confidence: 92%
“…In addition to hepatic homing there was also significant homing to the small intestine. In the current article, Neumann et al7 demonstrate that priming of CD4+ T cells by LSEC resulted in a T‐cell phenotype that promoted homing to the intestine and the GALT, and this was largely dependent on very specific molecular events (Fig. 1).…”
mentioning
confidence: 57%